ERCP-associated infected intrahepatic pancreatic pseudocyst. (2019) - Angsubhakorn, Natthapon; Laub, Leo; Keenan, Joseph C.
Abstract: Introduction: Pancreatic pseudocysts are abnormal mature collections of pancreatic fluid that can develop in association with acute or chronic pancreatitis. Here, we share the discovery of an infected hepatic subcapsular pseudocyst of the pancreas causing septic shock following endoscopic retrograde cholangiopancreatography (ERCP). Presentation of Case: A 55-year-old woman with ethanol-related chronic pancreatitis and biliary stricture was transferred to the ICU for hypotension 8 hours following ERCP. Examination revealed mild right upper quadrant tenderness without sign of peritonitis. Laboratory studies were notable for leukocytosis (14.6 k/L) and slightly elevated serum lipase (489 U/L). Abdominal CT scan revealed a previously undescribed subcapsular fluid collection. She underwent CT-guided percutaneous subcapsular drainage with return of opaque yellowish fluid. Fluid analysis showed elevated lipase of 62, 901 U/L with cultures positive for ESBL Escherichia coli, Streptococcus constellatus, and Enterococcus faecium . Discussion: A majority of pancreatic pseudocysts develop in peripancreatic regions, while, in a recent study, over a quarter of cases were found in usual sites. The management of subcapsular pseudocysts has not been standardized and often involves endoscopic or percutaneous drainage. Operative intervention is reserved for severe infection or rupture in patients with intrahepatic pseudocysts. Rarely do subcapsular pseudocysts become infected. In this case, we postulate the pseudocyst became seeded by bacteria during ERCP resulting in infection and then sepsis. Conclusion: This case report highlights an atypical presentation of pancreatic pseudocyst as well as a rare septic complication of ERCP.